VARIATION OF UPPER LIMBS SPECIFIC REPETITION SPEED IN ELITE ATHLETES OF QWAN KI DO MARTIAL ART AS A RESULT OF SPECIFIC TRAINING - Cojocariu A.; Oprean A.; Ungurean B. (ALTIUS ACADEMY Foundation - Faculty of Physical Education and Sports, 2017)
The purpose of the current research is to highlight the effects of physical training, conducted in the pre-season and season periods, on the specific repetition speed of the upper limbs, in the martial art of Qwan Ki Do. We have started from the assumption that by using a judicious planning and proper acting systems, we can improve significantly the specific repetition speed of the upper limbs in Qwan Ki Do. The experiment took place throughout a period of around eight weeks, and it included 19 athletes (8 female athletes and 11 male athletes), components of the national Romanian team, who trained in that period for participating in the European Championship. The important progresses recorded in both tests support the efficiency of the physical training program used regarding the manifestation of the speed of repetition, thus creating the premise of improving the efficiency of athletes during competitions.